2015
DOI: 10.1209/0295-5075/110/27007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of spin lattice coupling in MnTiO 3 : An x-ray diffraction study

Abstract: Here we investigate the temperature evolution of the structural parameters of a potential magnetoelectric material, MnTiO3. The experimental results reveal interesting temperature dependence of the c/a ratio and the Mn-O bonds which can be divided into three regions. In region I (300 K to 200 K), the above parameters are seen to decrease with decrease in temperature due to thermal effect. In the region II (200 K to 95 K), the decrement in the structural parameters are reduced due the competing intra layer anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…In the case of Ca 3 Co 2 O 6 compound, Mossbauer studies have also shown similar behaviour 16 . Similarly, in the case of quasi two dimensonal MnTiO 3 compound, our structural studies have shown clear signature of the onset of the magnetism within the ab-plane stabilizing at higher temperature than the onset of the magnetism between the planes 17 .…”
Section: Resultssupporting
confidence: 65%
“…In the case of Ca 3 Co 2 O 6 compound, Mossbauer studies have also shown similar behaviour 16 . Similarly, in the case of quasi two dimensonal MnTiO 3 compound, our structural studies have shown clear signature of the onset of the magnetism within the ab-plane stabilizing at higher temperature than the onset of the magnetism between the planes 17 .…”
Section: Resultssupporting
confidence: 65%
“…So, here the lattice parameter a is showing a very less deviation from the linear thermal behaviour up to the lowest temperature 26K. But for x=0 compound the situation is different 12 .…”
Section: Resultsmentioning
confidence: 77%
“…In the recent study done by H. J. Silverstein et al it has been proposed that the local spin lattice coupling is not weak and it is much more important for the magnetoelectric properties of this compound 13 . In our previous study 12 , the Mn-O, Mn-Mn and Ti-O bonds are showing significant changes across the region of intraand inter-layer antiferromagnetic interactions. The changes in Mn-O and Mn-Mn bonds across the onset temperature for 2D and 3D AFM is understandable but the changes in the Ti-O bonds at these temperature regions is not understandable .…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Within the layer (intra-layer), two Mn spins interact to each other through O ion via superexchange interaction and between the layer (inter-layer) through two O ions via super-superexchange interaction 11 . The intra-layer interactions are stronger than the inter-layer interactions.…”
Section: Resultsmentioning
confidence: 99%